Pengaruh Kepemimpinan, Kemampuan Intelektual dan Lingkungan Kerja terhadap Kinerja Pegawai - Vivi Candra; Ernest Grace; Marto Silalahi; Efendi Efendi; Sudung Simatupang (Universitas Batanghari, 2022)
The study tested the leadership variable, intellectual ability and work environment on employee performance at the Tanah Jawa District Office, Simalungun Regency, North Sumatra, which amounted to 32 employee. The study used quantitative and qualitative methods . The results showed that the questionnaire data instrument items were declared valid and reliable. The regression equation produces a positive correlation between the variables of leadership, intellectual ability and work environment on employee performance with the work environment variable having the greatest relationship to employee performance. Partially (t test) shows leadership has a significant influence on employee performance, intellectual ability has a significant influence on employee performance, work environment has a significant influence on employee performance. Simultaneously the variables of leadership, intellectual ability and work environment have a positive and significant influence on performance This shows that leadership, intellectual ability and work environment when running well in an organization and being able to become a carrying capacity for employees will have a positive impact on employee performance.